Delivery Capability as a Key Driver of PPP Geothermal Energy Project Completion: Evidence from Kenya (Global Journal of Human-Social Science, 2025)
Abstract not found
Keywords: public-private partnership (PPP); geothermal energy; delivery capability; project completion; renewable energy; dynamic capability theory